Immune Modulation to Improve Survival of Viral Pneumonia in Mice - Wali, Shradha; Flores, Jose R.; Jaramillo, Ana M.; Goldblatt, David L.; Pantaleón García, Jezreel; Tuvim, Michael J.; Dickey, Burton F.; Evans, Scott E. (American journal of respiratory cell and molecular biology, 2020)
Viral pneumonias remain global health threats, as exemplified in the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic, requiring novel treatment strategies both early and late in the disease process. We have reported that mice treated before or soon after infection with a combination of inhaled Toll-like receptor (TLR) 2/6 and 9 agonists (Pam2-ODN) are broadly protected against microbial pathogens including respiratory viruses, but the mechanisms remain incompletely understood. The objective of this study was to validate strategies for immune modulation in a preclinical model of viral pneumonia and determine their mechanisms. Mice were challenged with the in the presence or absence of Pam2-ODN treatment. Virus burden and host immune responses were assessed to elucidate Pam2-ODN mechanisms of action and to identify additional opportunities for therapeutic intervention. Enhanced survival of pneumonia with Pam2-ODN treatment was associated with reductions in lung virus burden and with virus inactivation before internalization. We noted that mortality in sham-treated mice corresponded with CD8 T-cell lung inflammation on days 11-12 after virus challenge, after the viral burden had declined. Pam2-ODN blocked this injurious inflammation by minimizing virus burden. As an alternative intervention, depleting CD8 T cells 8 days after viral challenge also decreased mortality. Stimulation of local innate immunity within the lungs by TLR agonists early in disease or suppression of adaptive immunity by systemic CD8 T-cell depletion late in disease improves outcomes of viral pneumonia in mice. These data reveal opportunities for targeted immunomodulation to protect susceptible human subjects.